2016
DOI: 10.1620/tjem.240.287
|View full text |Cite
|
Sign up to set email alerts
|

Increased Postural Sway and Changes in the Neuromuscular Activities of the Ankle Stabilizing Muscles at Ovulation in Healthy Young Women

Abstract: Lateral ankle sprains are one of the most common injuries among the physically active subjects. Ankle inversion-eversion laxity is greater and dynamic postural control is less in women compared with men. The purpose of this study was to examine differences in postural sway and its effects on the neuromuscular activities of the ankle stabilizing muscles during the menstrual cycle in young women. Fourteen young women with regular menstrual cycles participated in this experiment. Postural sway and electromyograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 43 publications
(68 reference statements)
4
29
0
Order By: Relevance
“…This would support the previous evidence pointing to a greater reduction in balance ability and tremor during ovulation period. A previous study also showed greater ankle laxity at ovulation than in other phases of the menstrual cycle [19]. All these evidence indicates that, there is general muscle, ligament laxity during the period of ovulation which supports the physiological change during rutu kala, 'Srasta kukshi, akshi moordhajaam'.…”
Section: Srasta Kukshi Akshi Moordhajaam (Laxity/flaccidity/ Posturasupporting
confidence: 57%
See 1 more Smart Citation
“…This would support the previous evidence pointing to a greater reduction in balance ability and tremor during ovulation period. A previous study also showed greater ankle laxity at ovulation than in other phases of the menstrual cycle [19]. All these evidence indicates that, there is general muscle, ligament laxity during the period of ovulation which supports the physiological change during rutu kala, 'Srasta kukshi, akshi moordhajaam'.…”
Section: Srasta Kukshi Akshi Moordhajaam (Laxity/flaccidity/ Posturasupporting
confidence: 57%
“…As estrogen levels peak during the ovulatory phase, significant increase in knee laxity have been detected. Various studies have investigated the effect of menstrual cycle on laxity of the ligaments and knee stabilizing muscles such as quadriceps and hamstring [19].…”
Section: Srasta Kukshi Akshi Moordhajaam (Laxity/flaccidity/ Posturamentioning
confidence: 99%
“…A recent study found that there was significantly greater postural sway during ovulation than during the follicular phase of the menstrual cycle Lee and Yim 2016). When women had a reduced capacity to control postural sway during ovulation, neuromuscular control of balance relied more on the TA than was seen during the follicular phase to compensate for ankle laxity.…”
Section: Discussionmentioning
confidence: 99%
“…The GPower 3.1 software (Heinrich-Heine-University Düsseldorf, Düsseldorf, Germany) was used to calculate the sample size needed using a moderate effect size of 0.85 between the two different menstrual cycle phases, with an alpha error probability of 0.05 and a power of 0.85 Lee and Yim 2016). A sample size of 15 participants was required to provide a statistical power of 86.4%.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation